2016
DOI: 10.5539/cco.v5n1p25
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Seed Localization for Nonpalpable Breast Lesions in a Community Hospital Setting

Abstract: Purpose: To compare the positive margin rates for women with nonpalpable breast tumors whom had wire localization compared to radioactive seed localization in a small community hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The analysis of our first 48 RSL patients (Wheeler et al, 2016) indicated the specimen weight was significantly larger for the RSL patients (average of 63 g) compared to the WL patients (average of 33 g; p=0.02). Since a larger specimen size could cause an inferior cosmetic result, it was encouraging that with the added experience accumulated with the second year of the RSL program, the difference in the specimen size no longer was significant, with a geometric mean of 32.78 g for the RSL patients compared to 30.26 for the WL patients, p-value 0.553.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of our first 48 RSL patients (Wheeler et al, 2016) indicated the specimen weight was significantly larger for the RSL patients (average of 63 g) compared to the WL patients (average of 33 g; p=0.02). Since a larger specimen size could cause an inferior cosmetic result, it was encouraging that with the added experience accumulated with the second year of the RSL program, the difference in the specimen size no longer was significant, with a geometric mean of 32.78 g for the RSL patients compared to 30.26 for the WL patients, p-value 0.553.…”
Section: Discussionmentioning
confidence: 99%
“…We reported on our initial 2014 experience comparing 48 RSL patients and 36 WL patients from our community hospital (Wheeler et al, 2016). Our initial positive margin rate was not statistically different between the WL (8.3%) and RSL (10.4%) patients, but the specimen weight was larger for the RSL patients (63 g) than for the WL patients (33 g; p = 0.02).…”
mentioning
confidence: 92%